Changing inter-occupational competencies in the wake of the digital shift : Perspectives for the regulatory and implementation levels - Zinke, Gert [Verfasser] (My University, 2019)
"Between 2016 and 2018, a project team at BIBB conducted occupation screenings as a part of the BMBF/BIBB initiative 'VET 4.0 - Qualifications and competencies of skilled workers for the digitalised work of tomorrow'. The impacts of digitalisation were investigated for 14 recognised training occupations. The present article describes the approach adopted in the project and pools findings from the various sub-studies. The focus is directed towards competencies that are evaluated as being particularly important in cross cutting terms. The article concludes by outlining a proposal for how such competencies can be fostered within the framework of an altered didactic design to which training regulations are already according consideration." (Author's abstract ; BIBB-Doku)
Veränderte berufsübergreifende Kompetenzen infolge des digitalen Wandels
Keywords: S 6 Berufsbereiche; G 1.2.3.2 Anforderungen & Bedarfe; Ausbildungsberuf; Berufsbild; Digitalisierung; Einflussfaktor; Berufsanforderung; Qualifikationsanforderung; Qualifikationswandel